English Antibacterial Power of the Patikan Kebo Plant (Euphorbia hirta) Against Leaf Blight Bacteria (Xanthomonas oryzae) - Meysya Putri; Ernin Hidayati; Suripto Suripto (Postgraduate, University of Mataram, 2025)
Bacterial leaf blight (BLB) is a significant disease of rice plants. It is caused by the Gram-negative bacterium Xanthomonas oryzae and often leads to yield losses. Excessive use of synthetic chemicals to control BLB has raised concerns over resistance and chemical residues. Therefore, natural alternatives are needed, such as Euphorbia hirta, which is traditionally used as a medicinal plant. This study aimed to determine the inhibitory power of E. hirta extracts against X. oryzae and to identify the presence of flavonoids, tannins, and saponins. Plant extracts were prepared by ethanol maceration, hot-water infusion ( 90 °C), and fresh squeezing. Antibacterial activity was evaluated by the well diffusion method on Mueller-Hinton Agar with concentrations of 25–100% (v/v), using chloramphenicol as positive control. Inhibition zones were measured after 24–120 h. The results showed that all preparations inhibited X. oryzae, with ethanol extract producing the strongest activity (10.65–15.94 mm), followed by infusion (3.09–6.31 mm) and fresh-juice (1.50–4.85 mm), compared to chloramphenicol (21.40 mm). Phytochemical tests confirmed flavonoids, tannins, and saponins in all extracts. In conclusion, E. hirta demonstrates antibacterial potential against , with ethanol extract being the most effective.